2020
DOI: 10.1159/000505932
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Bevacizumab plus Paclitaxel versus Bevacizumab plus Capecitabine for HER2-Negative Locally Recurrent or Metastatic Breast Cancer

Abstract: <b><i>Background:</i></b> The aim of the current study was to estimate two protocols for HER2-negative locally recurrent or metastatic breast cancer patients, bevacizumab combined with paclitaxel versus bevacizumab combined with capecitabine, from the economic view. <b><i>Methods:</i></b> The process of HER2-negative locally recurrent or metastatic breast cancer treated with bevacizumab combined with paclitaxel or bevaciz­umab combined with capecitabine made up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…After removing duplicates, we screened 226 records and assessed 138 full-text articles based on inclusion and exclusion criteria. Eventually, 92 pharmacoeconomic evaluations were included in the review and underwent data extraction (figure 1), detailed information on included studies can be found in online supplemental table 2 19–110…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, we screened 226 records and assessed 138 full-text articles based on inclusion and exclusion criteria. Eventually, 92 pharmacoeconomic evaluations were included in the review and underwent data extraction (figure 1), detailed information on included studies can be found in online supplemental table 2 19–110…”
Section: Resultsmentioning
confidence: 99%
“…The crucial role of VEGF‐A in angiogenesis, which is a process involved in tumor growth and metastasis, led to the development and use of anti‐VEGF drugs in the treatment of colorectal, breast, cervical, brain, and lung cancer 27‐34 . Bevacizumab is a recombinant humanized monoclonal antibody that targets VEGF‐A, inhibits the VEGF‐VEGFR interaction, and the VEGF‐induced proliferative effect on endothelial cells 35 .…”
Section: Introductionmentioning
confidence: 99%